Incidence of complications in young-onset diabetes: Comparing type 2 with type 1 (the young diab study). (January 2017) - Amutha, Anandakumar; Anjana, Ranjit Mohan; Venkatesan, Ulagamathesan; Ranjani, Harish; Unnikrishnan, Ranjit; Narayan, K.M.V.; Mohan, Viswanathan; Ali, Mohammed K.
Highlights: Compared to T1DM, young T2DM had higher risk of developing microvascular complications. Higher complications rate in T2DM suggests it may be innately a more aggressive disorder than T1DM. Adequately controlling glucose levels, hypertension and lipids could help prevent complications. Abstract: Background: There is little data on the incidence of diabetes complications in young onset type 1 diabetes (T1DM) and type 2 diabetes (T2DM) in non European populations. Methods: From a tertiary diabetes centre, Chennai, India, we recruited 108 T1DM (defined by abrupt onset of symptoms or diabetic ketoacidosis, absent insulin reserve requiring insulin treatment) and 90 T2DM participants (defined by absence of ketosis, good beta-cell reserve, and good response to oral agents) who were diagnosed between the ages of 10 and 25 years, and without any evidence of diabetes complications at diagnosis. We estimated the incidence of various complications (median follow up of five years); retinopathy was defined by presence of at least one definite microaneurysm by retinal photography, nephropathy by urinary albumin excretion ⩾30 μg/mg of creatinine, neuropathy by vibration perception threshold ⩾20 V on biothesiometry, peripheral vascular disease by an ankle-brachial index <0.9, and ischemic heart disease (IHD) by history of myocardial infarction or coronary revascularization or Q waves on ECG or on drug treatment for IHD. Results: The mean ages at diagnosis of T1DM and T2DM participants were 17.1 ± 4.2 vs. 21.6 ± 3.6 years respectively. The incidence of various complications reported in numbers/1000 person years of follow up of T1DM and T2DM were: retinopathy 77.4 vs. 78.0/1000 person years, nephropathy, 62.0 vs. 58.8, neuropathy 7.8 vs. 13.9 and ischemic heart disease 1.2 vs. 5.4. In Cox regression analysis, after adjustment for age, glycated hemoglobin, systolic blood pressure and serum cholesterol, T2DM participants had 2.11 times (95%CI: 1.27–3.51) higher risk of developing any diabetes complication, compared to T1DM. Conclusions: Young-onset T2DM have a more aggressive disease course than T1DM.